THE CONCEPT OF PREPARING FUTURE TEACHERS OF MATHEMATICS AND COMPUTER SCIENCE FOR THE USE OF VIRTUAL VISIBILITY TOOLS IN PROFESSIONAL ACTIVITIES - Mulesa, Pavlo (Physical and Mathematical Education, 2023)
Formulation of the problem. The article reveals the concept of professional training of future teachers of mathematics and computer science for the use of virtual clarity in professional activities, Materials and methods. The basis of the study was the existing research on the training of teachers in mathematics and computer science, changes in the psychological perception of information by young people (visual content), and existing practices of their teaching. Theoretical methods of scientific knowledge were used: analysis of the results of theoretical research, generalization of youth training practices, and content analysis of Internet resources.Results. The leading ideas of the concept are: recognition of the value for the society of professional training of future teachers of mathematics and computer science for the use of virtual visual aids in professional activities; formation of the readiness of future teachers of mathematics and computer science to use means of virtual visibility in professional activities in accordance with the development of the educational industry and digital technologies, as well as taking into account the peculiarities of young people's perception of visual content; modernization of the process of professional training of teachers with an emphasis on visual technologies, materials and means in the information and educational environment of higher education institutions; acquisition in the process of professional training of primary experience in the use of means of virtual clarity in the educational process; taking into account the trends in the transformation of vocational education in the direction of improving the professionalism of future teachers of mathematics and computer science, humanization of higher education, creating an information and digital environment of an educational institution; ensuring personal professional development, self-development and self-improvement of teachers of mathematics and computer science throughout their lives, forms their positive motivation and ability to achieve a high level of readiness of future teachers of mathematics and computer science to use virtual clarity in professional activities; introduction of new forms of organization of the educational process, in particular, in the application of innovative educational ones that ensure the effectiveness of educational, methodological and organizational support; creative and creative activity of teachers of higher education institutions, which is aimed at expanding the subject functions of future teachers of mathematics and computer science to form their skills to generate new knowledge and technologies, develop an innovative professional and pedagogical product (services, methods, etc.), creatively approach their own pedagogical activities. The concept of training is revealed at the methodological, theoretical, and practical levels.Conclusions. The developed concept can become the basis for designing a pedagogical system for preparing future mathematics and computer science teachers to apply virtual clarity in professional activities.
Keywords: the concept of professional training; future teachers of mathematics and computer science; the use of virtual clarity; professional activity